Presidential Agenda Building and Policymaking: Examining Linkages Across Three Levels. Issue 1 (1st January 2016) - Kiousis, Spiro; Ragas, Matthew W.; Kim, Ji Young; Schweickart, Tiffany; Neil, Jordan; Kochhar, Sarabdeep
ABSTRACT: To investigate the role of strategic political communication in governing, this study comprehensively examined presidential agenda-building associations at three levels during the first six months of U.S. president Barack Obama's second term. Multiple presidential information subsidies, national news content, and policymaking activity were monitored. The results revealed solid support for all three levels of agenda-building (i.e., object salience, attribute salience, and network associations among objects or attributes), but the linkages with media coverage and policymaking were not uniform across information subsidy types. Based on the analysis, presidential news releases, blog posts, and presidential speeches were the most effective all-around strategic agenda-building tools for media management and policymaking purposes during this time period. The theoretical and practical implications are discussed.